Determination of Major and Trace Metals in Date Palm Fruit (Phoenix dactylifera) Samples Using Flame Atomic Absorption Spectrometry and Assessment of the Associated Public Health Risks - Feven Tamirat; Wondimeneh Dubale Adane; Merid Tessema; Endale Tesfaye; Gizaw Tesfaye (International Journal of Analytical Chemistry)
This study aimed to assess the concentrations of major and trace metals (Na, Ca, Fe, Zn, Ni, Mn, Cu, Cd, and Pb) in date palm fruit samples collected from diverse regions, including Afar (Ethiopia), Iraq, and Saudi Arabia, utilizing flame atomic absorption spectrometry (FAAS). The wet acid digestion method was employed for sample treatment, with optimization of the key parameters such as reagent volume ratio, oven temperature, and digestion time for analytical applications. Under the optimized parameters, average metal concentrations in date palm fruit samples ranged from 205–299, 134–320, 38.8–115, 25.1–42.2, 9.27–27.9, 7.11–16.3, and 0.002–1.15 mg/kg for Ca, Na, Fe, Ni, Zn, Mn, and Cu, respectively. Cd and Pb levels were below detection limits within the linear range. Generally, date palm samples exhibited higher Ca and Na contents and lower concentrations of Cu and Mn than other metals. Pearson correlation analysis revealed very strong positive correlations between Fe and Na, Na and Zn, Na and Mn, Ca and Zn, Fe and Ni, Fe and Mn, and Mn and Ni. Strong negative correlations were observed for Ni and Na, Fe and Cu, and Cu and Ni. Weak correlations were noted among Na and Cu, Ca and Fe, Ca and Ni, Ca and Mn, Ca and Cu, Fe and Zn, Ni and Zn, Zn and Mn, and Zn and Cu. A recovery study using the spiking method demonstrated acceptable percentage recoveries ranging from 91.6% to 97.8%. Health risk assessment, including chronic daily intake (CDI), hazard quotient (HQ), total exposure hazard index (HI), and carcinogenic risk (CR), indicated CDI, HQ, and HI values below 1.0, except for the HI value for Ni. This suggests that the metals pose no probable public health risk, with the absence of Cd and Pb in date palm samples affirming no carcinogenic threats associated with their consumption.